Comparison of clinical efficacy of two approaches for endoscopic lumbar fusion surgery in the treatment of single-segment lumbar spondylolisthesis - Li, Kun; Lin, Hang; Zhang, Zhibin; Meng, Xiangyu (Frontiers in Surgery, 2025)
ObjectivesLumbar Spondylolisthesis (LSP) is a frequently encountered degenerative disorder of the spine. Unilateral biportal endoscopy (UBE) and percutaneous endoscopy (PE) have each shown promising initial results in managing this condition. This study aimed to compare the clinical efficacy of unilateral biportal endoscopic lumbar interbody fusion (UBE-LIF) and percutaneous endoscopic lumbar interbody fusion (PE-LIF) in treating single-level LSP, with the objective of providing high-quality evidence to support clinical decision-making.MethodsA retrospective analysis was conducted on clinical records from 118 patients diagnosed with single-segment LSP who were treated at the Sixth Affiliated Hospital of Xinjiang Medical University between June 2021 and August 2023. Participants were categorized into two groups: UBE-LIF (n = 61) and PE-LIF (n = 57). Parameters assessed included operative duration, intraoperative blood loss, and postoperative levels of serum biomarkers, creatine kinase (CK) and C-reactive protein (CRP), measured on the third day following surgery. Furthermore, evaluations were made using the visual analog scale (VAS) for back and leg pain, and the Oswestry Disability Index (ODI), at baseline, as well as at 3 days, 3 months, 6 months, and 1 year postoperatively. Radiographic fusion rates and incidences of postoperative complications were also compared.ResultsAll procedures were successfully completed. Intraoperative blood loss was slightly higher in the PE-LIF group, without significant difference (P = 0.568). The UBE-LIF group had a shorter operative duration (P < 0.001). On postoperative day 3, the UBE-LIF group exhibited significantly lower CRP levels compared to the PE-LIF group (P = 0.009). Both treatment groups demonstrated marked improvement in VAS and ODI scores across all follow-up periods, with no statistically significant intergroup differences at any time point (P > 0.05). Fusion rates and the incidence of postoperative complications were similar between the two cohorts (P = 0.852; P = 0.527, respectively).ConclusionsLarge randomized controlled trials are needed to robustly examine the comparative efficacy of these surgical options for lumbar spondylolisthesis. UBE-LIF appears advantageous in reducing operative time and improving surgical field exposure, which may potentially lower anesthesia-related risks and decrease anesthesia complications. Future large randomized controlled trials are needed to robustly examine the comparative efficacy of these techniques